Coupled reactive flow and dissolution with changing reactive surface and porosity. (12th October 2019) - Altree-Williams, A.; Brugger, J.; Pring, A.; Bedrikovetsky, P.
Graphical abstract: Highlights: Analytical model of 1D reactive flow with varying reactive surface area porosity. Four-zone structure of mineral-dissolution flow pattern. Universal formula for the speed of full dissolution front. High agreement between laboratory and modelling data. Accounting for varying surface area improves the laboratory data matching. Abstract: Mineral dissolution flows in porous media occur in numerous industrial and natural processes. We investigate the effects of varying rock-liquid interface on mineral dissolution transport in porous media. The one-dimensional mineral-dissolution flow problem that accounts for varying reacting interface and porosity is essentially non-linear. However, a novel exact solution is derived. The exact solution reveals a four-zone structure of the flow pattern with typical mineral concentration curves in all zones. The exact solution allows for a simplified inverse solver, facilitating determination of the surface function from laboratory reactive flow tests. Accounting for surface area evolution in the governing system of equations allows for significant improvement of matching the experimental data if compared with the constant-surface model. Moreover, the comparison between the analytical model and laboratory data reveals high agreement. The values of equilibrium mineral concentration as obtained from the matching and by thermodynamic calculations exhibit close agreement.